2023
DOI: 10.1177/09737030231169699
|View full text |Cite
|
Sign up to set email alerts
|

Gender Diversity, Sustainable Development Goals and Human Resource Management Practices in Higher Education

Abstract: Based on a systematic literature review, this article analyses the issue of gender diversity in higher education institutions (HEIs) and explores the role of strategic human resource management practices in its management. Results indicate that HEIs do not deal with gender diversity and challenges in achieving sustainable development goal-5 (SDG-5) proactively but manage them with compliance and some affirmative actions. The study finds that the number of women holding top leadership positions is substantially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 83 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…This shows that subtle discrimination still occurs in the context of the country's higher education. A study by Pandit and Paul (2023) found that the number of women holding top leadership positions is low. This shows the need for gender diversity in leadership.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that subtle discrimination still occurs in the context of the country's higher education. A study by Pandit and Paul (2023) found that the number of women holding top leadership positions is low. This shows the need for gender diversity in leadership.…”
Section: Introductionmentioning
confidence: 99%